Engineering STING Nanoadjuvants for spatiotemporally-tailored innate immunity stimulation and cancer vaccination therapy - Fangmin Chen; Huijuan Zhang; Shiqin Li; Siyuan Ren; Lujia Huang; Zhixiong Cai; Lichen Yin; Mingyue Zheng; Xiaolong Liu; Zhiai Xu; Haijun Yu (Nature Communications)
Abstract Spatiotemporally-tailored activation of dendritic cells (DC) in lymph nodes (LN) remains a critical challenge for effective cancer vaccination therapy. In this study, we show that photo/sonodynamic effect can trigger the nuclear transcription factor-kappa B (NF-κB) and stimulator of interferon genes (STING) pathways activation in DC. We engineers a library of spatiotemporally-tailored STING nanoadjuvants (SNA) by conjugating the photo/sonosensitizer and STING agonist onto the biodegradable polypeptide, and co-assembling with charge-modified polypeptides. The combination of antigen-loaded SNA vaccine (SNVac) with laser irradiation or ultrasound stimulation (namely SNVac-L or SNVac-US) efficiently facilitates DC activation and induces antigen-specific CD8+ T cell response in vivo comparing to the free mixture of antigen with STING agonist. We further demonstrate that SNVac-L monotherapy or combination therapy with immune checkpoint blockade (ICB) elicits antitumor immunity to reduce tumor size and prevent tumor relapse in multiple mouse tumor models. This study thus provides a potential translational strategy for spatiotemporally-tailored innate immunity stimulation of DC to potentiate cancer immunotherapy.